2007
DOI: 10.1080/14767050701209560
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety during pregnancy: A risk factor for obstetric, fetal and neonatal outcome? A critical review of the literature

Abstract: Enhanced levels of depression and anxiety symptoms during pregnancy contribute independently of other biomedical risk factors to adverse obstetric, fetal and neonatal outcome. However, conclusions for women with mood or anxiety disorders are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
498
3
44

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 734 publications
(566 citation statements)
references
References 73 publications
21
498
3
44
Order By: Relevance
“…Pregnant women with depression and anxiety are more likely to suffer from pregnancy symptoms such as nausea and vomiting [115]. While Grigoriadis et al [116] found no correlation between depression and pre-eclampsia, a more recent study [117] showed that depressive symptoms in pregnant women may be associated with an increased risk of pre-eclampsia.…”
Section: Effects Of Stress Depression and Anxiety In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women with depression and anxiety are more likely to suffer from pregnancy symptoms such as nausea and vomiting [115]. While Grigoriadis et al [116] found no correlation between depression and pre-eclampsia, a more recent study [117] showed that depressive symptoms in pregnant women may be associated with an increased risk of pre-eclampsia.…”
Section: Effects Of Stress Depression and Anxiety In Pregnancymentioning
confidence: 99%
“…While Grigoriadis et al [116] found no correlation between depression and pre-eclampsia, a more recent study [117] showed that depressive symptoms in pregnant women may be associated with an increased risk of pre-eclampsia. Moreover, a number of studies have noted that depressive and anxious pregnant women consulted their doctors more often and were more likely to require pain relief during the birth [115]. Other perinatal complications arising from mild to clinically relevant symptoms of prenatal maternal stress, depression or anxiety can include premature delivery and low birth weight of the child [118][119][120].…”
Section: Effects Of Stress Depression and Anxiety In Pregnancymentioning
confidence: 99%
“…Blood-and injection phobia is also known to be associated with several co-morbid psychiatric conditions such as major depression, obsessivecompulsive disorder, panic disorder and posttraumatic stress disorder (PTSD) (Bienvenu and Eaton, 1998;Goisman et al, 1998). Maternal stress due to psychopathological factors such as depression and anxiety during pregnancy may constitute a risk for adverse pregnancy and perinatal outcomes (Alder et al, 2007;Li et al, 2009;Lou et al, 1994;O´Connor et al, 2002;Rodriguez and Bohlin, 2005). A recent study by Wisner concluded that continuous untreated depression in pregnant women was associated with preterm birth rates exceeding 20 % (Wisner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hier scheint eine streßbedingte erhöhte Aktivität der mütterlichen Hypothalamus-Hypophysen-Nebennieren-Achse verantwortlich zu sein [1], [10].…”
Section: Risikenunclassified